2023
DOI: 10.3390/antibiotics12060973
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant (MDR) Urinary Tract Infections Associated with Gut Microbiota in CoV and Non-CoV Patients in a Urological Clinic during the Pandemic: A Single Center Experience

Viorel Dragos Radu,
Radu Cristian Costache,
Pavel Onofrei
et al.

Abstract: The aim of the study was to compare the profile of COVID-19 (CoV)-infected patients with non-COVID-19 (non-CoV) patients who presented with a multidrug-resistant urinary tract infection (MDR UTI) associated with gut microbiota, as well as analyze the risk factors for their occurrence, the types of bacteria involved, and their spectrum of sensitivity. Methods: We conducted a case–control study on patients admitted to the urology clinic of the “Parhon” Teaching Hospital in Iasi, Romania, between March 2020 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Regarding MDR infections, we found a lower percentage of them compared with other studies, which is probably explained by the lower incidence of possible risk factors (age, presence of urinary catheters, multiple hospitalizations, etc.). Although the group with sepsis had a higher statistically significant percentage of MDR UTIs compared with the non-sepsis group, this incidence is lower than in other reports [35]. The fact that we could not objectify any germs in urine culture in 25% of the cases, can also be explained by the fact that antibiotic treatment was initiated in many cases in other hospitals from which patients were transferred.…”
Section: Discussioncontrasting
confidence: 73%
“…Regarding MDR infections, we found a lower percentage of them compared with other studies, which is probably explained by the lower incidence of possible risk factors (age, presence of urinary catheters, multiple hospitalizations, etc.). Although the group with sepsis had a higher statistically significant percentage of MDR UTIs compared with the non-sepsis group, this incidence is lower than in other reports [35]. The fact that we could not objectify any germs in urine culture in 25% of the cases, can also be explained by the fact that antibiotic treatment was initiated in many cases in other hospitals from which patients were transferred.…”
Section: Discussioncontrasting
confidence: 73%
“…Reflux pyelonephritis can be a serious complication that can quickly lead to urosepsis in the absence of adequate antibiotic treatment [30]. However, as in other studies [28,31], the incidence of symptoms associated with double-J catheters in our study was much lower than the nearly 80% reported in other studies [13,25]. We did not find, as reported in other studies [32], that multiple ESWL sessions are required in patients with double-J stents to achieve the same effect as in patients without stents.…”
Section: Discussionmentioning
confidence: 89%
“…The administration of multiple ESWL sessions prolongs the time to achieve stone-free status and thus increases the risk of reflux, pyelonephritis, and double-J syndrome, as emphasized in other studies [13,[27][28][29]. Reflux pyelonephritis can be a serious complication that can quickly lead to urosepsis in the absence of adequate antibiotic treatment [30].…”
Section: Discussionmentioning
confidence: 97%
“…With regard to potential risk factors, we analyzed the presence of urinary catheters at the time of diagnosis, a recognized factor for increasing the incidence of MDR UTI [53], such as urethral catheters, double-J ureteral catheters, percutaneous nephrostomy catheters, cystostomy catheters, and percutaneous ureterostomy catheters. Regarding the presence of urinary catheters, we analyzed patients with catheters inserted earlier than one month ago and over one month separately in the two groups, knowing that the presence of catheters is a risk factor for bacterial colonization and the subsequent occurrence of infections.…”
Section: Outcome Measuresmentioning
confidence: 99%